Numerical simulation and modeling of carbon nanotubes - Wong, Chee How (2008)
The discovery of carbon nanotubes has triggered a significant amount of interest. Since then, much research has been done on these new forms of carbon because of its exceptional physical properties, which has been revealed in various theoretical and experimental studies. The focus of this thesis is on the mechanical and thermal properties of carbon nanotubes. A detailed study of the mechanical and thermal properties of carbon nanotubes is described in this thesis by employing molecular dynamics simulation. In this research, a parallelized molecular dynamics computer program based on MPI library and FORTRAN 77 computer language is developed to assist in the simulation of the carbon nanotubes. Throughout the whole of this research, Brenner’s “second-generation” empirical potential is used to describe the many-body short-range interatomic interactions, while the long-range non-bonded interactions is described using van der Waals forces characterized by Lennard-Jones (12,6) potential.